Effect of Heat Stimulation on Circulating Irisin in Humans - Park, Tae-Hwan; Lee, Hye-Jin; Lee, Jeong-Beom (Frontiers in Physiology, 2021)
High temperatures lead to oxidative stress. The aim of the study was to determine whether heat stimulation-induced hyperthermia can increase the level of circulating irisin. Twenty one healthy female subjects (age, 26.3 ± 2.71 yr; height, 162.1 ± 3.15 cm; weight, 54.2 ± 3.86 kg; and body surface area, 1.57 ± 0.11 m2) not taking contraceptives participated in this study. All experiments were performed individually for each participant when they were in the early proliferative menstrual phase. In an automated climate chamber (25 ± 0.5°C), the heat load was applied via half-body immersion into a hot water bath (42 ± 0.5°C). 5-min break was provided every after 5 mins of immersion and the total passive heating time was 30 mins. Tympanic temperature (Tty) and skin temperature (Ts) were measured. Mean body temperature (mTb) was calculated. Blood samples were collected before and immediately after immersion. Levels of irisin, cortisol, creatine kinase (CK) and lactate dehydrogenase (LDH) were analyzed. Tty, mTb and serum irisin levels increased after hot water immersion. The blood levels of cortisol, CK and LDH were also elevated after hot water immersion. Heat stimulation might increase the levels of circulating irisin in humans in response to oxidative stress.